Digital literacy impact on students’ performance/ Wan Nor Haliza Wan Mokhtar, Norhayati Hussin and Shahrul Nadzmi Mohd Shahari - Wan Mokhtar, Wan Nor Haliza; Hussin, Norhayati; Mohd Shahari, Shahrul Nadzmi (Faculty of Information Management, 2024)
This paper discusses on the transmission of the learning session from face to face to online learning. The study reveals the digital literacy level among students besides some of them still not aware of the importance of online learning that could help in their academic performances. There were issues where students face difficulties when searching for information effectively. The study was conducted to identify digital literacy among UiTM students in seeking the information they need for their studies from the electronic databases. The study sets out to examine the digital literacy level among students and to determine the relationship between the effect of digital literacy and student performance. Using survey data from students of UiTM, the study found out that effort expectancy, social influence and technology tool skill have a positive interaction effect on the outcome variable. The paper has fulfilled the objectives of the study which is related to the digital literacy level among UiTM students.